Resource based strategic groups and their performance implications: An exploration of the English Premier League - Lesforis, Kieran (2009)
Given the amount of comment in the press regarding the existence of distinct groups of teams within the Premier League, this study aimed to assess whether teams can be grouped on their resource endowments and if group membership has performance implications. The results gleaned from the research are inconclusive. Whilst the study is able to show that group membership does have performance implications these results are not robust. Sustained competitive advantage can be explained through industry level effects and firm specific characteristics rather than teams associated group membership. The results cast doubt on the relevance for grouping teams to explain persistent intra-industry performance differences.